Publishing WWII aerial photographs in geographical and library information systems - Verhelst, Elisabeth; Missel, Liesbeth; Vanmeulebrouk, Bas; Rip, Frans I. (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2012)
The Library of the Dutch Wageningen University and Research centre houses a collection of aerial photographs taken by the Allied Air Forces. The collection is part of a project that aims to publish these images in  a user friendly way so that they are accessible to a wide audience. This paper describes the nature of the collection and its particular requirements for publication, as well as the design and development of the application for collection presentation. The collection’s geographic characteristics dictated that the collection be presented together with other geographic materials such as digital historical maps and actual aerial photos. To create this information compilation, technologies from geographical information management were combined with technologies from library automation. This involved mainly metadata specification and management, but also usability design.